2001
DOI: 10.1083/jcb.200109063
|View full text |Cite
|
Sign up to set email alerts
|

Implication of a novel multiprotein Dam1p complex in outer kinetochore function

Abstract: Dam1p, Duo1p, and Dad1p can associate with each other physically and are required for both spindle integrity and kinetochore function in budding yeast. Here, we present our purification from yeast extracts of an ∼245 kD complex containing Dam1p, Duo1p, and Dad1p and Spc19p, Spc34p, and the previously uncharacterized proteins Dad2p and Ask1p. This Dam1p complex appears to be regulated through the phosphorylation of multiple subunits with at least one phosphorylation event changing during the cell cycle. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
150
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 43 publications
6
150
0
1
Order By: Relevance
“…First, Ask1 was phosphorylated in a cell cycle dependent manner giving rise to an altered electrophoretic mobility. During the course of these studies, this was also observed by Cheeseman et al 23 We observed that the timing of phosphorylation correlated well with the timing of Cdc28 activity in vivo. Furthermore, arresting cells in G 1 , S or M with drugs gave phosphorylation patterns consistent with the known levels of Cdc28 activity during those periods of the cycle.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…First, Ask1 was phosphorylated in a cell cycle dependent manner giving rise to an altered electrophoretic mobility. During the course of these studies, this was also observed by Cheeseman et al 23 We observed that the timing of phosphorylation correlated well with the timing of Cdc28 activity in vivo. Furthermore, arresting cells in G 1 , S or M with drugs gave phosphorylation patterns consistent with the known levels of Cdc28 activity during those periods of the cycle.…”
Section: Discussionsupporting
confidence: 87%
“…It is composed of at least 9 protein components, including Ask1, Dam1, Duo1, Dad1, Dad2, Dad3, Spc19, Spc34 and Hsk2 (Helper of Ask1) (YDR320C-A, Li and Elledge, in preparation), all of which are essential. [23][24][25] The kinetochore is not a static structure, but a dynamic one that must undergo substantial regulation to insure that proper microtubule attachment and segregation of chromosomes occur. Two key aspects of kinetochore function are the capture of microtubules and the bipolar attachment to microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…The S. cerevisiae kinetochore complex is composed of four subcomplexes: MIND, NDC80, COMA, and Ctf19 (De Wulf et al, 2003). In addition, the DASH complex is localized at the kinetochore and the spindle and is required for spindle attachment to the kinetochore (Cheeseman et al, 2001;Li et al, 2002). The S. cerevisiae DASH complex is composed of 10 proteins that localize at the kinetochore and the spindle (Miranda et al, 2005;Westermann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In this organism, mitotic spindles have been shown to be highly compromised in various mutants of the Dam1 complex (8,9,16,24). All 10 proteins of the Dam1 complex are essential for viability, localized at the KT throughout the cell cycle, and help in chromosome segregation by forming rings around the MTs in S. cerevisiae (48).…”
mentioning
confidence: 99%